EFFECT OF THE QUALITY OF FINANCIAL STATEMENTS, FOREIGN OWNERSHIP, FREQUENCY OF AUDIT COMMITTEE MEETING, AND SPECIALTY INDUSTRIAL EFFICIENCY INVESTMENT OF AUDITORS - Muslimah Nur Islami (JAAF (Journal of Applied Accounting and Finance), 2017)
This study aims to demonstrate the influence of the quality of financial statements, foreign ownership, the frequency of audit committee meetings, and the auditor industry specialization to the efficiency of investment. This study population is a company listed on the Indonesia Stock Exchange except banks and securities companies in 2009-2013. The samples in this study using purposive sampling method. The samples used for this study is total 561 companies. Hypothesis testing is done by multiple linear regression. The findings of this study are: 1) foreign ownership is significant positive effect on the efficiency of investment, 2) the frequency of audit committee meetings significant positive effect on the efficiency of investment, 3) industry specialization auditor negative effect not exhibited significantly to the efficiency of investment, and 4) the quality of financial statements significant negative effect on the efficiency of investment.